ANALISIS UNSUR INTRINSIK DAN UNSUR EKSTRINSIK NOVEL “DIA ADALAH KAKAKKU” KARYA TERE LIYE - Yantidiana Danur; Ida Ayu Made Wedasuwari; I Komang Widana Putra (JIPBSI (Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia), 2021)
This study aims to describe the intrinsic and extrinsic elements in the novel Dia Is Kakakku by Tere Liye. The method in this research uses qualitative analysis methods. Based on the data analysis, the intrinsic elements contained in Tere Liye's novel Dia Is My Kakakku are (1) the theme in Tere Liye's Dia Is My Kakakku novel tells the love of an older brother, (2) the main character in Tere Liye's Dia Is my Kakakku novel. namely Laisa, while the additional characters are Mamak, Dalimunte, Ikanuri, Wibisana, Yashinta, Wak Burhan, Cie Hui. (3) The setting is divided into two, namely the setting of the place covering the Lahambay Valley, Jungle Forest, Upper Village, Sub-District City, river, house, schools, airports, hospitals and the time setting in this story is at 19:30 local time. (4) language style, namely metamonia language style, (5) "he" third person point of view (6) The plot/plot used is the situational stage, the conflict and conflict stages decrease, the emergence of conflicts, (7) the mandate is to fight hard, be patient , unyielding, and responsible like Laisa who did her best to raise her four siblings with Mamak Lainuri. The extrinsic elements contained in the novel Dia Is My Kakakku are (1) the background of the author, namely the biography of the author of the novel, (2) the socio-cultural situation of the author and its influence on the literary work created, namely the author in making the novel (3) the values contained in the novel. namely moral values, cultural values, social values, religious values.